Accompagner les initiatives citoyennes dans le cadre d’un projet de revitalisation d’une commune rurale : le cas de Volonne - Séverine Bonnin-Oliveira; Emeline Hatt (Territoire en Mouvement)
This article deals with the recomposition of relations between public actors and citizens in the definition and the management of rural village sustainable planning projects, based on the analysis of the case of Volonne (Alpes-de-Haute-Provence). In a form of extension of the participatory dynamic initiated during the creation of the Ecodistrict, combining consultation, cooperation and co-building mechanisms, this rural municipality has seen the emergence of a multi-faceted citizen engagement studied in this research. In this perspective, we question the ability of rural municipalities to support and sustain citizens’initiatives in their efforts to transform the built environment and to develop “living together” in rural areas. The research shows the diversity of citizens' initiatives and their contribution to the improvement of the living environment but also the need to change traditional policy frameworks. The association of public actors and citizens calls for adjustments, articulations that remain partly to be found in order to respond to the difficulties of coordination or to the risk of shortening initiatives around a small group of participants.